Evaluation of the hydroxyethyl starch stabilizing agent, Vetstarch, in the preservation of canine cerebrospinal fluid samples. (19th March 2020) - Peterson, Lindsey N.; Christian, John A.; Bentley, R. Timothy; Moore, George E.; Thomovsky, Stephanie A.
Abstract: Background: A challenge of cerebrospinal fluid (CSF) analysis is the time‐dependent degradation of nucleated cells, impeding accurate interpretation. CSF additives have been used to delay cell degradation; however, stabilizing agents, including serum, can alter microprotein levels. Objectives: This study aimed to determine if the hydroxyethyl starch, Vetstarch, is effective at preserving nucleated cell morphology in CSF compared with the saline diluent or serum without altering microprotein levels. Methods: CSF samples were collected from 26 dogs. Samples were divided into four aliquots. One aliquot was analyzed immediately (control). The remaining three aliquots were mixed with either saline, fetal calf serum, or Vetstarch before storage at 4°C. Nucleated cell differentials, protein concentrations, and cell morphology scores were analyzed 48 hours later. A cell morphology score of 1 indicated no cellular degeneration; a score of 4 indicated severe degeneration. Results: Samples stored in serum, saline, and Vetstarch exhibited poorer mean (±SD) morphology scores (2.4 ± 0.7, 2.6 ± 0.8, and 2.7 ± 0.9, respectively) compared with controls (1.9 ± 0.4). Samples stored in saline and Vetstarch demonstrated higher percentages of unrecognizable cells, with a median of 28 (range 0‐100) and 27 (0‐100), respectively; samples stored in serum had a median of 14 (range 0‐67) unrecognizable. Microprotein levels of samples stored in Vetstarch were dependent on the method of protein analysis. Serum significantly increased microprotein levels. Conclusions: Vetstarch does not reduce time‐dependent cellular degeneration compared with the saline diluent or serum and is, therefore, not recommended as a stabilizing agent for canine cerebrospinal fluid.